Pelatihan Tata Kelola Surat Dinas dalam Upaya Peningkatan Tertib Administrasi Desa - Ismiyati, Hengky Pramusinto, Indri Murniawaty (Universitas PGRI Madiun, 2019)
Purpose of devotion is to improve the quality of public services effectively and efficiently. with the program tertibadministrasi governance Department letter. Main piority of patner that needed in the village at Singroojo District, Kendal Regency is providing knowledge, insight, and training about handling letters in governance. Second priority of devotion is achieving handling official letter, and helping to improve the internal and external of public quality. Agreement between partner and dedication team is doing the exposure material (socialization), training (technical guidance) and direct while mentoring practice. Socializing and training related about the knowledge, insight, and skills in handling official letter service. Mentoring related constraints that faced by participants in practice of handling official letter service.